Consequences of climate change damages for economic growth. A dynamic quantitative assessment - Dellink, Rob; Lanzi, Elisa; Chateau, Jean; Bosello, Francesco; Parrado, Ramiro; de Bruin, Kelly (Paris, 2014)
"This report focuses on the effects of climate change impacts on economic growth. Simulations with the OECD’s dynamic global general equilibrium model ENV-Linkages assess the consequences of a selected number of climate change impacts in the various world regions at the macroeconomic and sectoral level. This is complemented with an assessment of very long-run implications, using the AD-RICE model. The analysis finds that the effect of climate change impacts on annual global GDP is projected to increase over time, leading to a global GDP loss of 0.7% to 2.5% by 2060 for the most likely equilibrium climate sensitivity range. Underlying these annual global GDP losses are much larger sectoral and regional variations. Agricultural impacts dominate in most regions, while damages from sea level rise gradually become more important. Negative economic consequences are especially large in South and South-East Asia whereas other regions will be less affected and, in some cases, benefit thanks to adjustments from international trade. Emissions to 2060 will have important consequences in later decades and centuries. Simulations with the AD-RICE model suggest that if emissions continue to grow after 2060, annual damages of climate change could reach 1.5%-4.8% of GDP by the end of the century. Some impacts and risks from climate change have not been quantified in this study, including extreme weather events, water stress and large-scale disruptions. These will potentially have large economic consequences, and on balance the costs of inaction presented here likely underestimate the full costs of climate change impacts. More research is needed to assess them as well as the various uncertainties and risks involved. However, this should not delay policy action, but rather induce policy frameworks that are able to deal with new information and with the fact that by their nature some uncertainties and risks will never be resolved."